Searching for backbones — an efficient parallel algorithm for the traveling salesman problem - Schneider, Johannes; Froschhammer, Christine; Morgenstern, Ingo; Husslein, Thomas; Singer, Johannes Maria (Computer physics communications, 1996)
The Traveling Salesman Problem (TSP) plays an important role in Operations Research, Applied Mathematics and Computational Physics. We investigated it using a stochastic approach. Studying several solutions of a special TSP we found that many parts of a good solution are the same in all other good solutions for this problem. In this paper we discuss an efficient parallel method to reduce the TSP to a smaller one by finding these backbones and eliminating them to get even better solutions in a very short time and a few observables of interest corresponding to this parallel approach.